Induction of an exceptionally high-level, nontranslated, Epstein-Barr virus-encoded polyadenylated transcript in the Burkitt's lymphoma line Daudi. - Gao, Y (1997)
An Epstein-Barr virus transcript (designated D-HIT [Daudi high-level-inducible transcript]), constitutively expressed at low levels in the Burkitt's lymphoma (BL)-derived cell line Daudi, can be induced with tetradecanoylphorbol acetate or n-butyrate or, in combination, to about 1% of the levels of high-molecular-weight RNAs in cells. The transcript can also be induced in some other EBV-positive BL-derived cells but to a much lesser extent, particularly in lines that can give rise to productive infection. D-HIT is viral in origin and is composed largely of repetitive sequence. It is polyadenylated but mainly nuclear in location and is highly structured, sensitive only to double-strand-specific RNase. It is endogenously expressed in interferon-sensitive Daudi strains but not in an insensitive strain, Daudi 100K. D-HIT contains a part of a viral open reading frame (designated LF3, and deleted in the prototype B95-8 strain), using an internal polyadenylation (AAUAAA) sequence as a signal to specify processing of its 3' end. In Daudi cells, the promoter contains a putative hinge structure, as found in some interferon-inducible genes and c-myc. Since D-HIT lies adjacent to, probably even encompassing, one of the two viral lytic origins (D(R)) of replication, it may have a role in the regulation of DNA replication. Alternatively, or in addition via its double-stranded structure, D-HIT may play a regulatory role in interferon pathways. Its promoter could be of value for studying expression in constructions containing heterologous genes.